KLAUSA RELATIF BAHASA ARAB DALAM CERPEN ‘ALĪ BĀBĀ KARYA KĀMIL KĪLĀNĪ DAN CERPEN A’R-RĀ‘Ī A’SY-SYUJJĀ‘ KARYA ‘ATHIYYAH AL-IBRĀSYĪ (TINJAUAN SINTAKSIS) - Hasan, Muhamad (Arabic Letters and Department, 2014)
This research discuss about the Arabic relative clause with some problems of grammatical elements that can be relativized, relativization strategies that is used, and grammatical relations that is derived from the head of noun phrase in Arabic relative clause. The theory that is used in this research is the typology theory proposed by Comrie. The data that is used in this research is a written data which is taken from two short stories in Arabic that includes simple sentences. This research applied qualitative descriptive research method including three stages: data collection, data analysis, and presentation of the results. The method that is used in this research are the tapping technique, observation technique, and note technique as a method of providing data. Direct segmenting constituents technique, deletion technique, permutation technique, and expansion technique as the method of data analysis, and informal techniques as the method of presenting the results of the data analysis. The results showed that in Arabic sentences some position which can be relativized are subject, direct object, indirect object, and oblique. Elements of Arabic sentences that can be relativized apply the gap strategy, pronoun-retention, and relative-pronoun. The head of noun phrase is not only can be use in the same position of the second clause but also can be use in different position in each clause. Grammatical relation that is derived from the head of noun phrase from the relative clauses are (1) Subject of main clause and Subject of the relative clause; (2) Direct Object of main clause and Direct Object of relative clause; (3) Direct Object of main clause and Subject of relative clause; (4) non-Direct Object of main clause and Subject of relative clause; (5) Oblique of main clause and Oblique of relative clause; and (6) Oblique of main clause and Direct Object of relative clause.